Evolving perceptions regarding receiving orthopaedic care during the Coronavirus 2019 (COVID-19) pandemic: a follow-up survey. Issue 2 (March 2022) - Only, Arthur J.; Reams, Megan; Comadoll, Shea; Cunningham, Brian P.
Abstract : Background: As the Coronavirus 2019 (COVID-19) pandemic evolves, it is critical to understand how patients' feelings and perceptions have changed. The aim of this study was to understand current feelings and concerns about seeking and receiving orthopaedic care 9 mo into the global pandemic. Methods: Utilizing a survey developed to evaluate the attitudes and beliefs from healthcare respondents about receiving care during the COVID-19 pandemic, an updated and revised version, evaluating changes in perception of respondents 9 mo into the pandemic, was distributed to a group of panelists by email. Results: Out of 1200 individuals, 197 (16%) completed the survey. A majority of respondents reported high level of comfort in the immediate or near-term receiving care in an orthopaedic clinic, urgent care clinic specifically for orthopaedics, or in an emergency room. Six percent of respondents reported a delay in seeking orthopaedic care despite COVID-19 concerns that occurred between studies. Respondents reported their primary reason for delaying care was because of concerns for risk of COVID-19 exposure from other patients (83%). More than 75% of respondents stated they are "extremely" or "very" likely to get the COVID-19 vaccine when it becomes available to the public. Respondents had a generally negative outlook on pandemic efforts locally to globally. Conclusions: Despite dismal overall perceptions regarding the outlook of the pandemic; consumers are becoming increasingly comfortable obtaining orthopaedic care. The ability of healthcare providers and practices to adherence to safety protocols will remain essential to maintaining consumer trust and confidence. Level of Evidence: Level IV.